Knocking It Down and Mixing It Up: The Impact of Public Housing Regenerations - Hector Blanco; Lorenzo Neri (Institute of Labor Economics (IZA), 2023)
Due to their negative effects on surrounding neighborhoods, some countries have gradually been replacing distressed public housing developments with mixed-income housing. This paper studies the effects of such policies on local housing markets in London (UK), where local authorities demolished and rebuilt several public housing developments while adding market-rate units on-site. We show that these 'regeneration' programs lead to large increases in nearby house prices and rents over a six-year period, although house prices decrease farther away. The results are consistent with strong demand effects from observed amenity improvements near the buildings and downward price pressures from increased supply dominating in the broader area. We provide suggestive evidence that regenerations involving larger socioeconomic composition changes are associated with higher price increases.
Keywords: I38; H75; R23; R31; 330; public housing; mixed-income housing; house prices; amenities